Phase 1 study of the liposomal formulation of eribulin (E7389-LF): Results from the breast cancer expansion cohort. (June 2022) - Masuda, Norikazu; Ono, Makiko; Mukohara, Toru; Yasojima, Hiroyuki; Shimoi, Tatsunori; Kobayashi, Kokoro; Harano, Kenichi; Mizutani, Makiko; Tanioka, Maki; Takahashi, Shunji; Kogawa, Takahiro; Suzuki, Takuya; et al.
Abstract: Background: A liposomal formulation of eribulin, E7389-LF, may provide improved pharmacokinetics and allow increased access to tumour tissues. This expansion of a phase 1 study assessed the safety and efficacy of E7389-LF in patients with human epidermal growth factor receptor type 2-negative metastatic breast cancer. Methods: Patients received E7389-LF 2.0 mg/m 2 every three weeks. Tumour assessments were conducted every six weeks by the investigator by Response Evaluation Criteria in Solid Tumours v1.1. All adverse events were monitored and recorded. Serum biomarker assessments were conducted. Results: Of 28 patients included, 75.0% had hormone receptor-positive breast cancer (HR+ BC) and 25.0% had triple-negative breast cancer (TNBC). The most common grade ≥3 treatment-related treatment-emergent adverse events included neutropenia (67.9%), leukopenia (42.9%), thrombocytopenia (32.1%), and febrile neutropenia (25.0%). Rates of neutropenia and febrile neutropenia were lower among patients who received prophylactic pegfilgrastim. Objective response rate was 35.7% (95% confidence interval [CI]: 18.6–55.9) for all patients and 42.9% (95% CI: 21.8–66.0) for patients with HR+ BC. Median progression-free survival was 5.7 months (95% CI: 3.9–8.3). The median overall survival was 18.3 months (95% CI: 13.2–not estimable). Among the 54 biomarkers assessed, 27, including 5 of 7 vascular markers, were significantly altered by E7389-LF treatment from baseline to any time point. Conclusion: E7389-LF was tolerable and favourable antitumour activity was observed, particularly in patients with HR+ BC. Prophylactic pegfilgrastim can be considered in patients at high risk for neutropenia and febrile neutropenia. Clinicaltrials.gov number: NCT03207672 . Highlights: Liposomal eribulin, E7389-LF, has promising efficacy in patients with breast cancer. Neutropenia and febrile neutropenia were common adverse events. Prophylactic pegfilgrastim lowered incidence of neutropenia and febrile neutropenia. Vascular-related biomarkers changed from baseline over time.